Can cities provide butterfly-friendly habitats? - NURUL L. WINARNI; NURULIAWATI NURULIAWATI; BHISMA G. ANUGRA; ACHMAD R. JUNAID; SRI WIDAYANTI; ASLAN ASLAN; AGUNG NUGROHO; INDRAWAN MIGA; MUHAMMAD B. KURNIAWAN; MELLISSA LIESTANTI; RIZKA A. LUTFIANI; YULIA WULANDARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Winarni NL, Nuruliawati, Anugra BG, Junaid AR, Widayanti S, Aslan, Nugroho A, Miga I, Kurniawan MB, Liestanti M, Lutfiani RA, Wulandari Y. 2023. Can cities provide butterfly-friendly habitats? Biodiversitas 24: 2334-2341. Cities are progressively changed over time, creating land use changes with reduced green space areas. On the other hand, urban habitats offer a range of opportunities for biodiversity including butterflies which also act as an ecological health indicator. In Indonesia, like Jakarta Greater Area, or the so-called Jabodetabek which comprised Jakarta and its satellite cities, Bogor, Depok, Tangerang, and Bekasi, is highly urbanized. However, its capabilities to support the butterfly community are still little known. Thus, this paper aims to identify Jakarta Greater Area’s potential as urban habitat for butterflies through a citizen science approach namely KupuKita. The data were collected from June 2021 to November 2022. The survey used KupuKita platform, an online questionnaire established in 2021, which focused on three families, Nymphalidae, Papilionidae, and Pieridae. Its species richness, diversity and community pattern were analyzed consecutively by using Shannon-Wiener and Simpson’s Index. Next, the results were also analyzed towards the vegetation strata (grasses, shrubs, and trees) as observed during the data collection. The results suggested that Jakarta, Tangerang, and Bekasi have the least diverse butterfly community in comparison to Depok and Bogor. The butterfly community in Depok and Bogor was similar, both high in richness and diversity. Such similarity was potentially due to the wide arrays of remaining habitats that supported butterfly communities in three strata. The shrubs support more species richness rather than other strata. Bogor and Depok were potentially support more species in all three strata. Hence, because of the closely plant-butterfly relationships, vegetation interventions are crucial to increase the complexity of vegetation and create a butterfly-friendly habitat.